Prioritizinghydrological erosion-prone response units in Latyan catchment - Ali ahmad abadi; amir karam; Mohsen PourbashirHir (تحقیقات کاربردی علوم جغرافیایی)
Soil erosion in watersheds, causing problems such as the loss of agricultural land productivity and reduce soil surface layer, endangering the life of reservoirs and water utilities, loss of soil fertility, increasing flood, threatening human food security, etc. The negative effects of soil erosion, watershed management operations to improve care. According to the extent of the watershed and the lack of resources, prioritizing catchment areas due to the urgent need to implement watershed management plan is one of the solutions. Therefore, in this study the hydrological response units (HRU) were extracted in the Latyan dam basin. Hydrologic response units as a new approach can form smallest catchment study area. The need to prioritize the hydrological response of the watershed, using "Simple Additive Weighting and weighing "Analytical Network Process were performed. The results show that Most amount of erosion and Following the First Priority of Watershed's preserve is in the eastern part of the lake dam And the upstream basin with poor ranch land use, sedimentary-alluvial lithology and 26 degree of slop.